Diet compounds, glycemic index and obesity-related cardiac effects - Diniz, Yeda S. [UNESP]; Burneiko, Regina M. [UNESP]; Seiva, Fabio R. F. [UNESP]; Almeida, Flávia Queiroga Aranha de [UNESP]; Galhardi, Cristiano Machado [UNESP]; Novelli Filho, Jose Luiz V. B. [UNESP]; Mani, Fernanda [UNESP]; Novelli, Ethel L. B. [UNESP] (Elsevier B.V., 2008)
Background: Diet compounds may influence obesity-related cardiac oxidative stress and metabolic sifting. Carbohydrate-rich diet may be disadvantageous from fat-rich diet to cardiac tissue and glycemic index rather than lipid profile may predict the obesity-related cardiac effects.Materials and methods: Male Wistar rats were divided into three groups (n=8/group): (C) receiving standard chow (3.0 kcal/g); (CRD) receiving carbohydrate-rich diet (4.0 kcal/g), and (FRD) receiving fat-rich diet (4.0 kcal/g). Rats were sacrificed after the oral glucose tolerance test (OGTT) at 60 days of dietary treatments. Lipid profile and oxidative stress parameters were determined in serum. Myocardial samples were used to determine oxidative stress, metabolic enzymes, glycogen and triacylglycerol.Results: FRD rats showed higher final body weight and body mass index than CRD and C. Serum cholesterol and low-density lipoprotein were higher in FRD than in CRD, while triacylglycerol and oxidized low-density lipoprotein cholesterol were higher in CRD than in FRD. CRD rats had the highest myocardial lipid hydroperoxide and diminished superoxide dismutase and catalase activities. Myocardial glycogen was lower and triacylglycerol was higher in CRD than in C and FRD rats. Although FRD rats had depressed myocardial-reducing power, no significant changes were observed in myocardial energy metabolism. Myocardial beta-hydroxyacyl coenzyme-A dehydrogenase and citrate synthase, as well as the enhanced lactate debydrogenase/citrate synthase ratio indicated that fatty acid degradation was decreased in CRD rats. Glycemic index was positively correlated with obesity-related cardiac effects.Conclusions: Isoenergetic carbohydrate-rich and fat-rich diets induced different degree of obesity and differently affected lipid profile. Carbohydrate-rich diet was deleterious relative to fat-rich diet in the heart enhancing lipoperoxidation and shifting the metabolic pathway for energy production. Glycemic index rather than dyslipidemic profile may predict the obesity effects on cardiac tissue. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: obesity; diet compounds; glycemic index; heart; oxidative stress; metabolism